Kebebasan Beragama dalam Literatur Tafsir bi Al-Ma'tsur : Studi terhadap Tafsir Jami’ al-Bayan fi Tafsir al-Quran, Tafsir al-Quran al-Adzim dan al-Durru Al-Mantsur fi Tafsir bi al-Ma’tsur - Rozi, Fathur (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2024)
Beliefs (religion) are closely related to an individual's spiritual experience and cannot be imposed by anyone. The issue becomes different when the position of religion shifts from being private to entering the public sphere, making the choice of religion no longer an absolute fundamental right but subject to control, often leading to "threats" as religious conversion is considered a crime. Ultimately, practicing religion is no longer based on sincerity but rather coercion. In this study, the author limits the examination to the interpretation of bil ma'tsur written by three figures: Ibn Jarir al-Thabari, Abu al-Fida’ Ibn Kathir, and Jalaluddin al-Suyuti. The focus of the study is the tendency of bil ma'tsur interpretation in explaining verses about religious freedom related to theological categories in the religious tradition studied through literature review using content analysis techniques. The approach used is a comparative approach, aiming to portray the interpretations given by Thabari, Ibn Kathir, and al-Suyuti on verses about religious freedom. The research results show that there are four verses that share similarities in affirming the principle of religious freedom, emphasizing that every individual has the freedom to choose and believe in their religion. These four verses are Al-Baqarah verse 256, Yunus verse 99, Al-Kahfi verse 29, and Al-Kafirun verse 6. According to the views of al-Thabari, Ibn Kathir, and al-Suyuti, these verses convey an important message about respecting religious freedom and recognizing the right of every individual to choose their own beliefs, while emphasizing the values of truth and steadfastness in faith